Ultralow UV absorber content in 3D printed nanocomposites: maximizing printability and microwave absorption efficiency - David Tilve-Martínez; Wilfrid Neri; Jeanne Lessire; Benjamin Dulucq; Nicolas Vukadinovic; Benoit Berton; Jinkai Yuan; Philippe Poulin (JPhys Materials)
The increasing prevalence of electromagnetic wave exposure in our daily life, particularly within the 100 MHz–300 GHz range, necessitates advancements in microwave absorption materials. This study explores the utilization of 3D printing and VAT photopolymerization to optimize material properties for efficient microwave absorption. While electrically conductive nanocomposites comprising dielectric matrices and conductive fillers have shown promise, their 3D printability poses challenges particularly because of strong UV absorption by conductive fillers. This work addresses this challenge by employing weakly UV absorbing graphene oxide (GO) as a functional surfactant to stabilize single-walled carbon nanotubes (SWCNTs) in an acrylic polymer matrix. The GO particles adsorb at the SWCNT interface. GO remains insulating until in-situ thermal reduction to reduced GO (rGO). After reduction, rGO at the SWCNT interface minimize electrical contact resistance between nanotubes, promoting thereby high conductivity of the nanotube network. The high aspect ratio and conductivity of SWCNTs, combined with the transparency and amphiphilic nature of GO, result in nanocomposites with enhanced electrical conductivity and minimal UV absorption. This allows for the 3D printing of conductive formulations with SWCNT contents as low as 0.03 wt%. This ultralow UV absorber content ensures excellent printability, with maximum cure depths exceeding 100 µ m within seconds of UV irradiation. Moreover, the resulting nanocomposites exhibit promising microwave absorption properties in the S and Ku bands (2–4 and 12–18 GHz, respectively). Their reflexion losses, are below −10 dB over a 2.5 GHz bandwidth for a 4.75 mm thick layer. Emphasis is placed on the remarkable printability achieved in this study, as the microwave absorption properties remain unoptimized for specific applications.